Khitanan Masal di SMPN 1 Teluk Bayur Kecamatan Teluk Bayur - Dawami Buchori; Abdul Hakim; Taufik Temarwut; Tamam Rosid; Siti Munawaroh; Endah Susanti; Hasbiah Hasbiah (Pusat Riset dan Inovasi Nasional, 2025)
Circumcision is one of the important teachings in Islam and is considered obligatory for males according to the majority of scholars. In addition to its religious significance, circumcision also has medical benefits, particularly for male reproductive health. To support the implementation of Islamic law and improve child health among underprivileged families, the National Zakat Board (Baznas) of Berau Regency collaborated with the University of Muhammadiyah Berau to organize a mass circumcision program as a form of community service. The activity was held at SMPN 1 Teluk Bayur and involved 50 children living in the surrounding area. This study employed a qualitative descriptive approach, with data collected through observation, interviews, documentation, and literature review. The results indicate that the mass circumcision program had a positive impact by alleviating the financial burden on families, increasing public awareness of the importance of circumcision, and optimizing the use of zakat, infaq, and sadaqah (ZIS) funds for social and health programs. The program also highlighted the importance of synergy between zakat institutions and educational organizations in supporting community welfare in the post-pandemic era.